Identification and Localization of the First Known Proteins of the Trypanosoma cruzi Cytostome Cytopharynx Endocytic Complex - Chasen, Nathan Michael; Coppens, Isabelle; Etheridge, Ronald Drew (Frontiers in Cellular and Infection Microbiology, 2020)
Identification and Localization of the First Known Proteins of the Trypanosoma cruzi Cytostome Cytopharynx Endocytic Complex. Abstract: The etiological agent of Chagas disease, Trypanosoma cruzi, is an obligate intracellular parasite that infects an estimated 7 million people in the Americas, with an at-risk population of 70 million. Despite its recognition as the highest impact parasitic infection of the Americas, Chagas disease continues to receive insufficient attention and resources in order to be effectively combatted. Unlike the other parasitic trypanosomatids that infect humans (Trypanosoma brucei and Leishmania spp.), T. cruzi retains an ancestral mode of phagotrophic feeding via an endocytic organelle known as the cytostome-cytopharynx complex (SPC). How this tubular invagination of the plasma membrane functions to bring in nutrients is poorly understood at a mechanistic level, partially due to a lack of knowledge of the protein machinery specifically targeted to this structure. Using a combination of CRISPR/Cas9 mediated endogenous tagging, fluorescently labeled overexpression constructs and endocytic assays, we have identified the first known SPC targeted protein (CP1). The CP1 labeled structure co-localizes with endocytosed protein and undergoes disassembly in infectious forms and reconstitution in replicative forms. Additionally, through the use of immunoprecipitation and mass spectrometry techniques, we have identified two additional CP1-associated proteins (CP2 and CP3) that also target to this endocytic organelle. Our localization studies using fluorescently tagged proteins and surface lectin staining have also allowed us, for the first time, to specifically define the location of the intriguing pre-oral ridge (POR) surface prominence at the SPC entrance through the use of super-resolution light microscopy. This work is a first glimpse into the proteome of the SPC and provides the tools for further characterization of this enigmatic endocytic organelle. A better understanding of how this deadly pathogen acquires nutrients from its host will potentially direct us toward new therapeutic targets to combat infection.